Detektif Pangan Mengungkap Rahasia Dibalik Warna Jajanan pada Anak - Lenny Amelia HK; Muthia Juliani Utami Utami (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2026)
Students at Al Ma’soem Elementary School represent a group vulnerable to hazardous non-food dyes (such as Rhodamine B) due to the high consumption of brightly colored snacks and low food safety literacy. This issue is exacerbated by the lack of knowledge among local producers regarding Food Additive (BTP) regulations. The 'Food Detective' Program aims to enhance students' awareness and motor skills in identifying hazardous substances independently to foster more selective consumption behavior. Implementation utilizes experiential learning through visual socialization, simple science experiments (rapid tests) using natural indicators like turmeric, and evaluations via pre-tests and post-tests. Mentorship was also provided to canteen operators to transition to natural dyes. This initiative significantly improved student literacy, as evidenced by post-activity evaluation scores. Managerially, the program successfully established 'Food Detective' cadres as a sustainable internal school monitoring system. Furthermore, collaboration with canteen vendors in using natural alternatives (such as suji leaves or beets) has created a healthy canteen ecosystem.